South Africa’s Highly Cited Research on Medicinal Plants: A Scientometric Exploration of Impact and Innovation - KK, Mueen Ahmed; M, Chaman Sab (Journal of Data Science, Informetrics, and Citation Studies)
Background and Aim: This bibliometric study investigated High-impact Publications (HCPs) in South Africa’s Medicinal Plants research from 2021 to 2025. The primary aim is to map the scholarly landscape by identifying influential works, key authors, institutions, and emerging trends in the literature, highlighting medicinal plants. Methodology: This bibliometric analysis, a systematic search was extracted on Elsevier’s Scopus database, on 13, March 2025, to retrieve relevant data from 2021 to 2025. A total of 5,386 publication records were related to research on medicinal plants in Africa. These publications were sorted by the citations they received since their publication. Out of 5386 publications by Africa, only 62 publications were found to have received 100 to 2034 citations per paper. These 62 publications are presumed as HCs for this study. The data so collected was documented, tabulated, and analyzed using Microsoft Excel. VOSviewer and R Studio software were utilized for network visualization. Results: These publications were sorted by the citations they received since their publication. Out of 5386 publications by Africa, only 62 publications were found to have received 100 to 2034 citations per paper. These 62 publications are presumed as HCs for this study. This study reveals that high-impact publications, extensive international collaboration, and a strong preference for review articles characterize South African research on medicinal plants. Conclusion: This research provides a comprehensive overview of influential works and their contributions to the understanding of medicinal plants. It establishes a foundation for future study and underscores the critical need for ongoing investigation in this area to improve patient management and outcomes.
Keywords: Medicinal Plants; Bibliometrics study; VOSviewer; South Africa; Highly cited publications.